Transcriptomic Responses of Fusarium verticillioides to Lactam and Lactone Xenobiotics - Gao, Minglu; Gu, Xi; Satterlee, Timothy; Duke, Mary V.; Scheffler, Brian E.; Gold, Scott E.; Glenn, Anthony E. (Frontiers in Fungal Biology, 2022)
The important cereal crops of maize, rye, and wheat constitutively produce precursors to 2-benzoxazolinone, a phytochemical having antifungal effects towards many Fusarium species. However, Fusarium verticillioides can tolerate 2-benzoxazolinone by converting it into non-toxic metabolites through the synergism of two previously identified gene clusters, FDB1 and FDB2. Inspired by the induction of these two clusters upon exposure to 2-benzoxazolinone, RNA sequencing experiments were carried out by challenging F. verticillioides individually with 2-benzoxazolinone and three related chemical compounds, 2-oxindole, 2-coumaranone, and chlorzoxazone. These compounds all contain lactam and/or lactone moieties, and transcriptional analysis provided inferences regarding the degradation of such lactams and lactones. Besides induction of FDB1 and FDB2 gene clusters, four additional clusters were identified as induced by 2-benzoxazolinone exposure, including a cluster thought to be responsible for biosynthesis of pyridoxine (vitamin B6), a known antioxidant providing tolerance to reactive oxygen species. Three putative gene clusters were identified as induced by challenging F. verticillioides with 2-oxindole, two with 2-coumaranone, and two with chlorzoxazone. Interestingly, 2-benzoxazolinone and 2-oxindole each induced two specific gene clusters with similar composition of enzymatic functions. Exposure to 2-coumranone elicited the expression of the fusaric acid biosynthetic gene cluster. Another gene cluster that may encode enzymes responsible for degrading intermediate catabolic metabolites with carboxylic ester bonds was induced by 2-benzoxazolinone, 2-oxindole, and chlorzoxazone. Also, the induction of a dehalogenase encoding gene during chlorzoxazone exposure suggested its role in the removal of the chlorine atom. Together, this work identifies genes and putative gene clusters responsive to the 2-benzoxazolinone-like compounds with metabolic inferences. Potential targets for future functional analyses are discussed.